Efficacy and safety of 177Lutetium-prostate-specific membrane antigen therapy in metastatic castration-resistant prostate cancer patients: First experience in West Asia – A prospective study - Aghdam, Ramin Akbarian; Amoui, Mahasti; Ghodsirad, Mohammadali; Khoshbakht, Sepide; Mofid, Bahram; Kaghazchi, Fateme; Tavakoli, Mehrdad; Pirayesh, Elahe; Ahmadzadehfar, Hojjat (World Journal of Nuclear Medicine, 2019)
Prostate-specific membrane antigen (PSMA) is a transmembrane protein that is highly expressed on the surface of prostate cancer (PC) cells, making it an excellent radiotracer for both therapeutic and diagnostic purposes. In this prospective study, we investigated the efficacy and toxicity of 177Lutetium (Lu)-PSMA in metastatic castration-resistant PC (mCRPC) patients for the establishment and approval of this therapy in Iran. Fourteen mCRPC patients (mean age 70.57 ± 7.3 years) were treated with a single dose of 177Lu-PSMA. Complete blood count, liver function tests (aspartate aminotransferase and alanine aminotransferase), alkaline phosphatase levels, renal function tests (urea and creatinine), and prostate-specific antigen (PSA) levels were obtained for the patients at baseline and every 2 weeks. A majority of the patients (11 patients, 64.2%) experienced a decline in their PSA levels; in 5 (45.4%) of these patients, the PSA levels declined > 50%.The severity of pain decreased in 8 (57.1%) patients, and performance status was improved in 5 (45.4%) patients. The treatment was well tolerated, and no severe hematological or nonhematological side effects were observed. Our findings show that 177Lu-PSMA had a high efficacy and a low toxicity in an Iranian population and is a promising treatment option for PC patients.
Keywords: 177Lutetium; metastatic castration-resistant prostate cancer; prostate cancer; prostate-specific membrane antigen; radionuclide therapy; theranostic